Analysis of Identification Methods for the Viscoelastic Properties of Materials - Dietrich, L.; Turski, K. (Engineering Transactions, 1992)
A complete solution of the constitutive equations for a viscoelastic material described by Burgers model is presented under various initial conditions. Possibilities to determine the viscoelastic properties of materials for various loading patterns of a specimen are pointed out. Test results on asphalt mixture obtained under various loads and strain rates are discussed. Creep, cyclic deformations and constant strain rate loading are found to enable the viscoelastic properties to be determined in different ranges of strain rates. The obtained results of these types of tests provide a consistent spectrum of these properties as functions of the initial strain rates.